Standardization and classification of athletes` working capacity rates versus skill levels - Shirkovets, E. A.; Shustin, B. N. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyze correlations of the quantitative energy supply rates and their effects on competitive accomplishments. Conclusion. Statistical data analysis gives the means to assess and standardize the physical working capacity rates. The study data of that kind may be particularly beneficial for the cyclic sports where competitive performance is largely dependent on the athletes` aerobic resources.